Fumigant Toxicity of callistemon viminalis Essential Leaves Oils against Vinegar Fly, Drosophila melanogaster - Abdulhay, Hind Suhail (Asian Journal of Biological and Life Sciences, 2016)
The essential oils of Callistemon viminalis (Gaertn) were obtained using a Clevenger type apparatus through hydrodistillation. The essential oils were tested for fumigant toxicity against adults (1-3 day old) of Drosophila melanogaster. All toxicity tests were carried out under laboratory conditions set at 23 ±2ºC and 60% relative humidity (RH). Results showed that tested concentrations exhibited high toxicity effects on D. melanogaster adults and the high toxicity rate was concentration and time dependent. Lethal concentration values for 50% of D. melanogaster adults (LC50) were 56.57, 37.22 and 20.58 ml/L air, after 5, 10 and 24 h. respectively. The results of gas chromatography (GC) analysis indicated that the essential oil extracted from the leaves of C. viminalis, contain 1,8-cineole (57.35%), α-pinene (10.20%), aspartic acid (12.30%) and palmitic acid (15.65%). These results suggest that C. viminalis, oil could be a potential candidate as a fumigant for controlling vinegar fly D. melanogaster.
Keywords: Callistemon viminalis; Drosophila melanogaster; Essential oils; Insecticidal activity